Design parameters of Portuguese granitic residual soils obtained from DMT tests - Nuno Cruz (2012)
: Cemented soils are often seen as non-textbook materials, since they donŽt fit into the usual behavior of transported soils in the light of classical Soil Mechanics theories. This fact creates several problems on the interpretation of in-situ test results, when the classical approaches are used, limiting the application of common in-situ tests. Departing from a long experience in characterizing Portuguese granitic soils with Marchettis Dilatometer (DMT) a large calibration box (CemSoil Box) was constructed to work with artificially cemented silty sands, aiming the evaluation of static penetration influence in the loss of cementation strength, and the overall effects on the stiffness response, giving rise to adequate correlations for deriving design parameters. The experience was based in the development of artificially samples tested in triaxial cell and in the CemSoil Box, where blades could be pre-installed and pushed in. Water level, suction and seismic velocities were monitored during the experience. The final results allowed for the establishment of specific correlations to derive strength (cohesion intercept and angles of shearing resistance) and stiffness (deformability and small strain shear modulus) parameters, as well as a specific methodology for controlling suction influence on the respective results.